2015
DOI: 10.1016/j.ydbio.2015.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin signals through integrin α5β1 to regulate cardiovascular development in a cell type-specific manner

Abstract: Fibronectin (Fn1) is an evolutionarily conserved extracellular matrix glycoprotein essential for embryonic development. Global deletion of Fn1 leads to mid-gestation lethality from cardiovascular defects. However, severe morphogenetic defects that occur early in embryogenesis in these embryos precluded assigning a direct role for Fn1 in cardiovascular development. We noticed that Fn1 is expressed in strikingly non-uniform patterns during mouse embryogenesis, and that its expression is particularly enriched in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 69 publications
5
66
0
Order By: Relevance
“…2F): 29-42% penetrance (Table S2). Cardiac NC contributes mesenchymal cells to the thymus, regulating morphogenesis of this organ (Bockman and Kirby, 1984); consistent with that, we found that 44% of mutant embryos had mild defects in thymus development (Chen et al, 2015). Taken together, these phenotypes are characteristic of many other mouse mutants with defective development or function of the cardiac NC (Hutson and Kirby, 2007).…”
Section: Ablation Of Fn1 In the Nc Results In Cardiovascular Abnormalsupporting
confidence: 87%
See 4 more Smart Citations
“…2F): 29-42% penetrance (Table S2). Cardiac NC contributes mesenchymal cells to the thymus, regulating morphogenesis of this organ (Bockman and Kirby, 1984); consistent with that, we found that 44% of mutant embryos had mild defects in thymus development (Chen et al, 2015). Taken together, these phenotypes are characteristic of many other mouse mutants with defective development or function of the cardiac NC (Hutson and Kirby, 2007).…”
Section: Ablation Of Fn1 In the Nc Results In Cardiovascular Abnormalsupporting
confidence: 87%
“…The high evolutionary conservation of Fn1 and the essential role of Fn1 in cardiovascular development suggested that enriched expression of Fn1 in specific embryonic regions is biologically significant. The studies described in this paper and in our earlier publication (Chen et al, 2015) reveal requisite, cell typespecific functions of Fn1 in embryogenesis and cardiovascular development.…”
Section: Role Of Fn1 and Integrin α5 In Nc Development And Cardiovascsupporting
confidence: 57%
See 3 more Smart Citations